Alumina Supported Nickel-iron-ruthenium based Catalyst for Dry Reforming of Methane - Alhajri, Nawal; Albuali, Mohammed (Current Catalysis, 2022)
Introduction: Alumina-supported nickel-iron-ruthenium-based catalyst with a high surface area (200 m2 g-1) was synthesized via an impregnation method and tested for dry reforming of methane. Methods: The prepared catalyst was characterized by different analytical techniques, such as Xray diffraction, X-ray fluorescence, N2 sorption, environmental scanning electron microscopy, and X-ray photoelectron spectroscopy (XPS). Result: The results revealed that the catalyst contains 2.5 wt.% Ni, 2 wt.% Fe and 1.8 wt.% Ru. Conclusion: The catalytic tests showed that the prepared sample exhibits remarkable catalytic activity towards methane dry reforming, with high conversion of methane and carbon dioxide reaching up to 92% and 89%, respectively, at 800°C.
Keywords: nickel-iron ruthenium